In Situ and Laboratory Testing of Boom Clay at Shallow Depths in Belgium - Maria Konstadinou; Etienne A. Alderlieste; Cor Zwanenburg; Cihan Cengiz; Anderson Peccin da Silva; Charlotte J. W. van Verseveld (Geotechnics)
The shear strength and compression properties of stiff Boom clay from Belgium at a depth of about 16.5 to 28 m were investigated by means of cone penetration and laboratory testing. The latter consisted of index classification, constant rate of strain, triaxial, direct simple shear and unconfined compression tests. The Boom clay samples exhibited strong swelling tendencies. The suction pressure was measured via different procedures and was compared to the expected in situ stress. The undrained shear strength profile determined from cone penetration tests (CPTs) was not compatible with the triaxial and direct simple shear measurements, which gave significantly lower undrained shear strength values. Micro-computed tomography (μCT) scans of the samples showed the presence of pre-existing discontinuities which may cause inconsistencies in the comparison of the laboratory test results with in situ data. The experimental data gathered in this study provide useful information for analyzing the mechanical behaviour of Boom clay at shallow depths considering that most investigations in the literature have been carried out on deep Boom clay deposits.